2011
DOI: 10.1536/ihj.52.270
|View full text |Cite
|
Sign up to set email alerts
|

Distal Reference Segment Luminal Gain Following Percutaneous Coronary Intervention for Chronic Total Occlusion

Abstract: SummaryPercutaneous coronary intervention (PCI) for chronic total occlusion (CTO) increases forward blood flow, possibly resulting in an increase in lumen diameter. We investigated the determinants of luminal gain at the distal reference segment following PCI for CTO. Forty-eight consecutive patients who underwent PCI for CTO were included in this study. Clinical and angiographic data were obtained at baseline and follow-up (mean follow-up period: 251 ± 73.6 days). Overall, the reference lumen diameter was 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…The present study also showed a significant negative linear correlation between LD at distal reference at post‐PCI and %LG (r = −0.57, p < 0.001), in the similar magnitude as previously reported (r = −0.5, p < 0.001) . Several factors are reported to be associated with greater late lumen enlargement such as lower low‐density lipoprotein cholesterol level, longer total occlusion duration, poor collateral flow grade, statin use, no resting hypokinesis in the territory supplied by the CTO, PHB on IVUS, and smaller LD at the distal reference . However, the predictors are not established yet except for the small distal reference at post‐PCI.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study also showed a significant negative linear correlation between LD at distal reference at post‐PCI and %LG (r = −0.57, p < 0.001), in the similar magnitude as previously reported (r = −0.5, p < 0.001) . Several factors are reported to be associated with greater late lumen enlargement such as lower low‐density lipoprotein cholesterol level, longer total occlusion duration, poor collateral flow grade, statin use, no resting hypokinesis in the territory supplied by the CTO, PHB on IVUS, and smaller LD at the distal reference . However, the predictors are not established yet except for the small distal reference at post‐PCI.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, cases without resting segmental hypokinesis tended to be more frequently observed in LAD than non‐LAD group (26 vs. 15%, p = 0.13), and LD at distal reference was significantly smaller in the LAD compared to the counterpart (1.83 ± 0.54 mm vs. 2.18 ± 0.63 mm, p = 0.002) at post‐PCI. These factors have been reported as predictors of late lumen enlargement, possibly affecting our results. However, multivariable analysis showed the CTO in the LAD as independent predictors.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Second, lesions with restenosis or re-occlusion were excluded, so it is uncertain whether the Park et al 1 and Ogita et al 16 reported clinical or angiographic predictors of LLG, but we did not find similar findings. Recent pathological studies have suggested a possible role of the IEM and media in coronary arterial lesions with spasm or vessel shrinkage.…”
Section: Study Limitationsmentioning
confidence: 58%
“…It is well known that the lumen size of the reference segments distal to the chronically occluded or severely stenotic lesion may increase late after successful PCI of the culprit lesion. 1,15,16 A recent serial IVUS observational study, 1 as well as an angiographic follow-up study, 16 demonstrated that the lumen area of the distal reference segments increases in 69% of the patients with successful recanalization of CTO at 6-month follow-up. Our results showing that LLG was detected in 59% of lesions are concordant with that.…”
Section: Discussionmentioning
confidence: 99%